Sistem Marketplace Penitipan Hewan Dengan Memanfaatkan Teknologi React Native - Grace Levina Dewi; Suhatati Tjandra (Widya Teknik, 2022)
Keeping animals is a very fun hobby because pets can be entertainment in itself to relieve fatigue from daily activities. But there are certain times, the owner doesn't have time to take care of the pet, especially if there are tasks out of town for a few days, or other activities. Pet care is a solution to keep pets taken care of while their owners don't have time to take care of them. Animal care provides care facilities for pets that are deposited. Currently, many provide animal care services with the aim of helping facilitate the search for the best animal care services and according to needs. Developed a mobile application system in the form of an animal care marketplace using React Native technology. The purpose of making this system is so that animal owners can find animal care centers according to their wishes. There are two users who play a role in this system, namely animal owners and animal day care workers. The animal owner's user system can determine a message schedule to entrust animals to the care feature and choose the cage to be occupied. The advantage of this feature is that pet owners can also know the condition of their pets, because each officer will send information. Through testing this system, it is known that there are about 73% of users who want to use this system. This system helps people who have pets not to worry about doing care.